ANALISIS KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMP PADA MATERI PYTHAGORAS - Angga Andriawan; Asti Sari Setiawati; Indah Puspita Sari; Siti Chotimah (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2018)
This study aims to analyze the critical thinking skills of junior high school students on Pythagoras material. Subjects in this study are students of class VIII-F in SMP Negeri 1 Ngamprah with the number of students 37 people. The method used in this research is qualitative descriptive. This type is chosen because it aims to describe the skills of students in solving problems of mathematical critical thinking independently. The research phase is divided into three, namely planning, implementation, and reporting. The technique of collecting data in the form of test. Data analysis techniques based on indicators of mathematical critical thinking skills that has been determined by researchers include: (1) identifying the concepts used in problem solving, (2) formulating an action (strategy, tactics, or approach) in solving problems, (3) providing arguments or reasons for answering and solving problems, and (4) evaluating evidence or decisions taken in solving the problem. The results obtained quantitatively show that the level of mathematical critical thinking skills of students in SMP Negeri 1 Ngamprah in solving the problems on Pythagoras material still falls into the low category. The evidence from the percentage of each indicator with the highest rate of only 61%. Some factors influence the level of students critical thinking skills, including the preparation of incomplete and appropriate strategies, provide arguments without showing the truth, and the students' accuracy in working on the questions.